2016
DOI: 10.1016/j.jsxm.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Definitions of Sexual Dysfunctions in Women and Men: A Consensus Statement From the Fourth International Consultation on Sexual Medicine 2015

Abstract: Introduction: Definitions of sexual dysfunctions in women and men are critical in facilitating research and enabling clinicians to communicate accurately. Aims: To present the new set of definitions of all forms of sexual dysfunction in women and men adopted by the Fourth International Consultation on Sexual Medicine (ICSM) held in 2015. Methods: Classification systems, including the International Classification of Diseases, 10th Edition and the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
297
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(316 citation statements)
references
References 5 publications
6
297
0
13
Order By: Relevance
“…Disorders of male sexual function are categorised in relation to desire, ejaculation, orgasmic and the most common, erectile function 3. The causes of erectile dysfunction can be classified mainly as organic, with a vascular, hormonal or neurogenic aetiology, or psychogenic where the aetiology is connected to psychiatric disorders, performance anxiety, interpersonal problems or concerns related to somatic disease, or a combination of the above.…”
Section: Introductionmentioning
confidence: 99%
“…Disorders of male sexual function are categorised in relation to desire, ejaculation, orgasmic and the most common, erectile function 3. The causes of erectile dysfunction can be classified mainly as organic, with a vascular, hormonal or neurogenic aetiology, or psychogenic where the aetiology is connected to psychiatric disorders, performance anxiety, interpersonal problems or concerns related to somatic disease, or a combination of the above.…”
Section: Introductionmentioning
confidence: 99%
“…The female sexual response consists of the following four phases: desire, arousal, orgasm, and resolution . Female sexual dysfunction is defined as the occurrence of changes in any one of these phases or the presence of pain that manifests itself in a persistent and recurring way …”
Section: Introductionmentioning
confidence: 99%
“…Studies in adult populations have revealed high prevalence of sexual dysfunction [5, 6], which, according to the International Classification of Disease (ICD-10) [7], encompasses a spectrum of symptoms including lack of sexual desire, lack of sexual pleasure, failure of genital response, orgasmic dysfunction, premature ejaculation and dyspareunia [2, 6]. This symptomatology follows the Masters and Johnson [8] and Kaplan [9] frameworks of the three-phase model of sexual response (desire, arousal, and orgasm), with the addition of sexual pain.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used instruments are the Female Sexual Function Index (FSFI) (19 items) for females [13] and the International Index of Erectile Function (IIEI) for males [14]. The FSFI instrument only covers a 4-week period, failing to distinguish transient from prolonged symptomatology among females while the IIEI instrument only focuses on erectile dysfunction omitting other functional dimensions of sexual activity among males [6]. None of these instruments assess aspects of sexual distress.…”
Section: Introductionmentioning
confidence: 99%